Size Effect in the Split Hopkinson Pressure Bar Experiment. Issue 1 (1st January 2022) - Nie, Hailiang; Ma, Weifeng; Ren, Junjie; Wang, Ke; Cao, Jun; Dang, Wei; Yao, Tian; Wang, Kang
Abstract: For many structures, their service environment is very strict, and the requirements for the impact resistance of materials are very high. Therefore, the dynamic testing method has important scientific significance and application value for practical engineering. Split Hopkinson pressure bar (SHPB) is one of the most common experimental methods for obtaining dynamic mechanical properties of materials. However, there is no uniform standard for the size of the bars and specimens used in the test. Theoretically, the size has little influence on the experimental results, but it has not been proved by experiments. This paper mainly studies the influence of device/specimen sizes of split Hopkinson pressure bar through experiments, it is demonstrated that the sizes of bars and specimen have little effect on experimental results.